Growing Calf and Show Steer Feed Management - Matt Hersom; Todd Thrift (EDIS)
AN254, a 9-page fact sheet by Matt Hersom and Todd Thrift, details feeds, feed management, and nutrient requirements for growing cattle with a view towards successful development of a quality show calf. Includes references. Published by the UF Department of Animal Sciences, October 2010.